To solve this problem you can use the distance formula. The distance between two points is given as:

`d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2}`

Plugging in the points (-1, 7) and (-2, 3), we see that

`d = \sqrt{(-2 - -1)^2 + (3 - 7)^2} = \sqrt{17} \approx 4.12`

Recalling the distance formula derivatived from the Pythagorean theorem,

d= sqrt((x1-x2)^2+(y1-y2)^2)

between two points (x1,y1),(x2,y2)

in this case, x1= -1 x2=-2 y1=7 y2=3 (You can change x1 and x2 around and y1 y2 around since squares cancel the negatives)

d=sqrt((-1+2)^2+(7-3)^2)

= sqrt(1+4^2)

= sqrt 17

The distance of the given two points is sqrt 17 units of length, or in decimal form, 4.12 units away from each other.

In this case, we omit the negative value since distance could NOT be negative.

We'll recall the formula that gives the distance between two points:

AB = sqrt[(xB-xA)^2 + (yB-yA)^2]

Let A(-1,7) and B(-2,3)

AB = sqrt[(-2+1)^2 + (3-7)^2]

AB = sqrt(1 + 16)

AB =sqrt17

**The requested distance between the given points is of sqrt17 units of length.**